Historical increases in land‐derived nutrient inputs may alleviate effects of a changing physical climate on the oceanic carbon cycle. (23rd August 2021) - Lacroix, Fabrice; Ilyina, Tatiana; Mathis, Moritz; Laruelle, Goulven G.; Regnier, Pierre
Abstract: The implications of climate change and other human perturbations on the oceanic carbon cycle are still associated with large uncertainties. Global‐scale modelling studies are essential to investigate anthropogenic perturbations of oceanic carbon fluxes but, until now, they have not considered the impacts of temporal changes in riverine and atmospheric inputs of P and N on the marine net biological productivity (NPP) and air–sea CO2 exchange (FCO2 ). To address this, we perform a series of simulations using an enhanced version of the global ocean biogeochemistry model HAMOCC to isolate effects arising from (1) increasing atmospheric CO2  levels, (2) a changing physical climate and (3) alterations in inputs of terrigenous P and N on marine carbon cycling over the 1905–2010 period. Our simulations reveal that our first‐order approximation of increased terrigenous nutrient inputs causes an enhancement of 2.15 Pg C year −1 of the global marine NPP, a relative increase of +5% over the simulation period. This increase completely compensates the simulated NPP decrease as a result of increased upper ocean stratification of −3% in relative terms. The coastal ocean undergoes a global relative increase of 14% in NPP arising largely from increased riverine inputs, with regional increases exceeding 100%, for instance on the shelves of the Bay of Bengal. The imprint of enhanced terrigenous nutrient inputs is also simulated further offshore, inducing a 1.75 Pg C year −1 (+4%) enhancement of the NPP in the open ocean. This finding implies that the perturbation of carbon fluxes through coastal eutrophication may extend further offshore than that was previously assumed. While increased nutrient inputs are the largest driver of change for the CO2 uptake at the regional scale and enhance the global coastal ocean CO2 uptake by 0.02 Pg C year −1, they only marginally affect the FCO2 of the open ocean over our study's timeline. Abstract : In our study, we account for land‐derived increases in nutrient inputs to the ocean originating from both perturbed riverine and atmospheric transport for 1905–2010. These increases in nutrient supply affect the carbon cycle of both the coastal and open ocean while partly alleviating effects arising from changes in the physical climate.